Research on the influencing factors and mechanism of AR e-commerce consumers’ purchase intention - Xiaodong Zhang; Pan Yang; Chunrong Guo; Pan He (PLoS ONE, 2026)
Against the backdrop of the digital economy and the increasing integration of virtual and physical consumption scenarios, augmented reality (AR) e-commerce reshapes the shopping experience by overlaying virtual information onto real-world contexts, thereby accelerating the industry’s shift from traffic-driven competition to experience-based competition. However, existing studies remain insufficient in explaining the underlying mechanism through which AR e-commerce influences consumers’ purchase intention, and the applicability of the stimulus–organism–response (S–O–R) framework in virtual–real integrated environments has not been adequately extended. Drawing on the S–O–R paradigm, this study conceptualizes four key AR-enabled characteristics—immersive virtual try-on, interactive product display, real-time fusion shopping, and personalized recommendation—as stimulus variables (S). Perceived value and brand attitude are modeled as organism variables (O), and purchase intention is treated as the response variable (R), forming an integrated conceptual model. Using survey data collected from 482 valid respondents, structural equation modeling (SEM) is employed to test the proposed relationships. The results indicate that all four AR stimuli indirectly enhance purchase intention by positively affecting perceived value and brand attitude. Among the stimulus dimensions, real-time fusion shopping exerts the strongest positive effect on perceived value (β = 0.290), whereas personalized recommendation shows the most pronounced effect on brand attitude (β = 0.295). In addition, perceived value and brand attitude play partial mediating roles, and brand attitude demonstrates a stronger direct effect on purchase intention (β = 0.449) than perceived value (β = 0.347). Theoretically, the present study systematically translates AR e-commerce technological attributes into stimulus dimensions within the S–O–R framework, thereby extending its explanatory boundary in virtual–real integrated settings and offering an integrated “technology–scenario–behavior” analytical lens. Practically, the findings provide actionable insights for e-commerce platforms and brand managers seeking to optimize AR-driven experience design and improve conversion outcomes.